Protection to native idleness, socially and not politically, considered. (Melbourne : James Caple, 1858)
Argument for the importance of cultivating and supporting refinement, the arts, leisure, etc. among the wealthy class in Victoria, for its importance in creating culture, etc. in Victorian society.
Ferguson, J.A. Bibliography of Australia
also available online
Keywords: Leisure class; Social classes; Melbourne (Vic.) -- Intellectual life; Melbourne (Vic.) -- Social life and customs -- 1851-1891.